Análisis organizacional en empresas de economía circular, un caso de estudio con Industrias Químicas FIQ SAS (2023)
The present study analyzes the innovation needs of an SME, for this specific case Industrias Químicas FIQ SAS, which is a circular economy company dedicated to the recovery of industrial solvents. During this study we carried out a gap analysis, identifying that in addition to innovation issues, the company had shortcomings in strategic planning. In this proposal, we suggest carrying out strategic planning exercises, together with methodologies for innovation processes, all of the above adequate and grounded in the size of the company, and putting our stamp on the appropriate approaches for SMEs. Concerning the above, it drawns as a great conclusion that FIQ is a company willing to accept recommendations in favor of improving its internal management and increasing its profitability.